Model for the preparation of a short list of candidate techniques for the prioritization of requirements - Bravo Loayza, E. Daniel (2018)
Prioritization of requirements is an important stage in the software development process. Technical stocks of prioritization of the requirements that must obtain the priorities that correspond to each participant and obtain a unified and prioritized list. Different techniques are sought in different projects. A preliminary step is to develop a list of candidate techniques from which a more appropriate technique is selected. In the bibliography consulted, the authors define a previous list, without specifying the criterion that was used for their pre-selection. A model for the preparation of a short list of techniques for the prioritization of requirements is proposed. Previously a review of the definition of requirement, stakeholder, requirements engineering, requirements management and its prioritization phase, as well as other related concepts. A model is proposed so that the elements comply with the candidate techniques, the implementation of the system in collaborative CMS tools. At the end, the evaluation process is included, which will validate the proposed model.